Symptoms in Children After Chemotherapy - Sevcan Atay Turan; Figen Işık Esenay; Menevşe Güven (Güncel Pediatri)
Introduction: Identification of symptoms resulted from chemotherapy in children. Materials and Methods: In this study 46 children and adolescents who had chemotherapy in a pediatric oncology clinic of an oncology hospital were included. Sociodemographic questionnaire and Memorial Symptom Assessment Scale (10-18 years) were used as data collection tool. Results: In this survey the mean age of children with cancer was 13.47±2.14 years and the majority of them (41.3%) were monitored with non-Hodgkin’s lymphoma diagnosis. The most common symptoms in children who had chemotherapy in hospital were fatigue (76.1%), feeling nervous (69.6%), alopecia (65.2%), nausea (60.9%) and feeling sad (60.9%), while the least common symptoms were swelling in the arms/legs (8.7%) and problems in urination (6.5%). The most troublesome symptoms were dizziness (66.6%), difficulty in swallowing (64.3%), pain (47.8%) and hair loss (43.4%). Conclusions: It was seen that the children still experience high prevalence of post-treatment symptoms, they had more intense psychological symptoms and physical symptoms caused more discomfort.